Effect of corrosion on printed circuit board - Muhammad Aminuddin, Adnan (2013)
Corrosion of electronic systems has been a significant issue in electronic industry nowadays. One of the most common corrosion type is the atmospheric corrosion. Therefore, even a small environmental impact can cause huge damages if the components are not well protected. When the device is in use, the large voltage gradients between points on a printed circuit board (PCBs) will accelerate the corrosion problems dramatically. The complexity of the atmosphere, as corrosion environment, results from atmosphere composition and from presence of some factors as pollutants, temperature, humidity, wind speed and direction. So, the objective of the study is to identify the effect of corrosion on solder joint and copper substrate in 0.5M Sulphuric acid (H2S0) in order to determine the corrosion rate of the substrate in duration time by using weight loss measurement method. Lead-free solder bump were used to form solder joint between lead-free solder Sn-3Ag-0.5Cu (SAC 305) solders with the plated copper substrate. The copper substrate surface finish was deposited by the electroless nickel. The result of study shows the corrosion on the substrate after immersed in 0.5M Sulphuric acid at 168 hours, 336 hours, and 504 hours. The effect of corrosion was increased with the time duration increased. The weight loss data indicated that the thickness of the substrate decreased with the time duration. The structure of the solder joint was analyze using scanning electron microscopy (SEM).